WP 3: Sustainable farming systems intensification for climate resilient decomposition of yield gaps - Baum, Michael; Lal Jat, Mangi; Nangia, Vinay; Devkota Wasti, Mina Kumari; Moussadek, Rachid; Gathala, Mahesh Kumar (International Center for Agricultural Research in the Dry Areas, 2022)
From Fragility to Resilience in Central and West Asia and North Africa (F2R CWANA) WP 3: Sustainable farming systems intensification for climate resilient decomposition of yield gaps Inception Workshop Morocco May 17, 2022.